EXPLORING RARE INTERSTITIAL LUNG DISEASES: INSIGHTS FROM HIGH-RESOLUTION COMPUTED TOMOGRAPHY - Dimitrijevikj, Kristina; Nikolova, Sonja; Pejkovska, Sava (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2024)
Interstitial lung diseases (ILDs) pose significant diagnostic and therapeutic challenges due to their diverse and intricate nature. This study investigated rare ILDs, such as cryptogenic organizing pneumonia, eosinophilic pneumonia, lymphocytic interstitial pneumonia, hypersensitivity pneumonitis, and Langerhans cell histiocytosis, identified through high-resolution computed tomography (HRCT) in N. Macedonia. A cohort of ten patients was recruited from the University Clinic for Pulmonology and Allergology in Skopje over a one-year period. HRCT scans were conducted using a 128-slice PHILIPS INCISIVE CT scanner, while clinical data were gathered from comprehensive medical records and questionnaires. Analysis revealed a gender distribution of 6 females and 4 males, with ages ranging from 18 to 78 years (mean age: 50±17.2 years), predominantly residing in urban areas. Notably, six patients reported cough symptoms, while dyspnea was present in nine individuals. HRCT findings encompassed reticular shadows, high and low attenuation, and trapped air, exhibiting diverse distribution patterns. This study contributes to elucidating the radiological patterns and distributions of rare ILDs, thereby enhancing diagnostic accuracy and facilitating effective management strategies.
Keywords: HRCT; ILDs; rare cases